Meat Quality Characteristics of Small East African Goats and Norwegian Crosses Finished under Small Scale Farming Conditions - W. A. Hozza; L. A. Mtenga; G. C. Kifaro; D. S. N. Shija; D. E. Mushi; J. G. Safari; E. J. M. Shirima (Asian-Australasian Journal of Animal Sciences, 2014)
The aim of the experiment was to study the effect of feeding system on meat quality characteristics of Small East African (SEA) goats and their crosses with Norwegian (SEA×N) goats finished under small scale farming conditions. Twenty four castrated goats at the age of 18 months with live body weight of 16.7±0.54 kg from each breed (SEA and SEA×N) were distributed in a completely randomized design in a 2×3 factorial arrangement (two breed, and three dietary treatments). The dietary treatments were; no access to concentrate (T0), 66% access to ad libitum concentrate allowance (T66) and 100% access to ad libitum concentrate allowance with 20% refusal (T100) and the experimental period was for 84 days. In addition, all goats were allowed to graze for 2 hours daily and later fed grass hay on ad libitum basis. Daily feed intakes were recorded for all 84-days of experiment after which the animals were slaughtered. Feed intake of T100 animals was 536 g/d, which was 183 g/d higher than that of T66 group. Supplemented goats had significantly (p<0.05) better feed conversion efficiency. The SEA had higher (p<0.05) hot carcass weight (8.2 vs 7.9 kg), true dressing percentage (54.5 vs 53.3) and commercial dressing percentage (43.3 vs 41.6) compared to SEA×N. There was no significant difference (p>0.05) for dressing percentage and carcass conformation among supplemented goats except fatness score, total fat depots and carcass fat which increased (p<0.05) with increasing concentrate levels in the diet. Increasing level of concentrate on offer increased meat dry matter with subsequent increase of fat in the meat. Muscle pH of goats fed concentrate declined rapidly and reached below 6 at 6 h post-mortem but temperature remained at 28°C. Cooking loss and meat tenderness improved (p<0.05) and thawing loss increased (p<0.05) with ageing period. Similarly, meat tenderness improved (p<0.05) with concentrate supplementation. Shear force of muscles varied from 36 to 66, the high values been associated with Semimembranosus and Gluteobiceps muscles. The present study demonstrates that there are differences in meat quality characteristics of meat from SEA goats and their crosses with Norwegian breeds finished under small scale farming conditions in rural areas. Therefore, concentrate supplementation of goats of both breeds improves meat quality attributes.